Development of the Korean Version of the Drooling Infants and Preschoolers Scale - Kyoung Chul Min; Mi Young Hong; Ickpyo Hong; Hee Soon Woo (Occupational Therapy International)
Objective. This study is aimed at translating and cross-culturally adapting the Drooling Infants and Preschoolers Scale (DRIPS) into Korean cultural context and examine the content validity and reliability of the Korean version, which is referred as K-DRIPS. Methods. An iterative forward-backward translation sequence of the DRIPS was performed by 20 Korean health professional experts (i.e., occupational therapists (OTs) and professors) with more than 10 years of experience. The study subjects were 77 children with cerebral palsy (CP) exhibiting drooling symptoms aged 2-7 years. They were recruited from two children’s rehabilitation hospitals in Korea and completed the K-DRIPS. The content validity and internal consistency of the K-DRIPS items were examined. Results. An assessment with 20 K-DRIPS items was adequately and cross-culturally adapted into Korea. All the items exhibited good content validity (content validity ratio range 4.00-4.95) and good internal consistency (Cronbach’s α=0.98). Conclusion. The study findings indicated that the K-DRIPS was successfully adapted to the Korean cultural context and demonstrated good psychometric properties. This instrument could be used for drooling assessment tool in Korean children with disabilities.